IDENTIFIKASI EFEKTIVITAS REAERASI MENGGUNAKAN MICROBUBBLE GENERATOR (MBG) PADA AIR EMBUNG - Yulianti, Tri (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2021)
The retention basin at the Faculty of Engineering Gadjah Mada University was built as a flooding control into the Code river and improving the water quality. The water entering the basin, especially in the dry season, is characterized as greywater due to the dense settlements around the university. The purpose of this study was to determine the effectiveness of reaeration process using a Microbubble Generator (MBG) to increase DO, with the aim of this leading to an improved water quality. The MBG aerator with submersible pumps was installed at a depth of 40 cm from the water surface and placed in the middle of the pond. The aerator was permanently turned on. In situ monitoring of DO was carried out using a seri Lutron WA-2017SD DO meter. The increasing DO correlated with the changes of the surrounding weather which impact on water and air temperature. At the time of DO data collection, the water temperature ranged from 24.5oC - 27oC and the change in DO measured at the inlet and outlet of the reservoir was in the range 0.3 - 1.1 mg/l, with the DO directly surrounding the aerator reaching up to 2.4 mg/l from the inlet. With the DO increased, the concentration of pollutant organic loads can be reduced and the nitritation and nitratation processes has taken place properly so that it has reduced the pollutant load before the water enters the Code river.